Effect of Ground Motion Horizontal Definition in Seismic Analysis and RC Moment Frame Structures in Mandalay Region - Khine Mon Myint; Ornthammarath, Teraphan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
Since Myanmar is one of the earthquake-prone zones in Southeast Asia, the seismic performance analysis is recommended in this region. Myanmar National Building Code, 2016which is adapted from ASCE 7-05 is stipulated to examine the analysis by the Federation of Myanmar Engineering Society (Fed. MES). The geometric mean of the two horizontal spectral accelerations is typically used by the earth scientists as the intensity measure for hazard analysis and early effort to account for the seismic design of the structure. Shortcoming of the geomean ground motion intensity definition, the maximum spectral acceleration of the two orthogonal components in any orientation is used in the recent ASCE 7-16 for structural design. In this study, the factors which are the ratio of maximum spectral acceleration (SaRotD100) to median spectral acceleration (SaRotD50) at discrete period is used to predict the maximum spectral acceleration over all orientations. The objective of the study is to analyze the effect of the two-horizontal definitionsin ground motion selection. The comparison of the regular and irregular shaped RC building structural responses is also explored with equivalent lateral force analysis (ELF), response spectrum analysis (RSA) and Linear response history analysis (LRHA). The final response results show the great potential in the performance-based design of the civil system.